TRADE NETWORKS AND MARITIME COMMODITIES IN THE SAMUDERA PASAI SULTANATE 13TH TO 15TH CENTURIES - Siregar, Isrina (Universitas Sultan Ageng Tirtayasa, 2023)
This article is research on one of the sultanates in the Archipelago, the Sultanate of Samudera Pasai. This research aims to discover the brief history of the Sultanate of Samudera Pasai, the trade network of Samudera Pasai with other nations, and the maritime commodities in the Sultanate of Samudera Pasai. The author in this paper uses literature or library research methods and historical research methods. Based on the research results, Samudera Pasai was located in the strategic Malacca Strait, which made Samudera Pasai the center of maritime trade between nations. Samudera Pasai was also known as a place of spice trade because it produced and sold much pepper. Pasai's strategic location in the Strait of Malacca established trade networks with other nations, especially the Indians and Chinese. The number of traders from various nations made all commodities or trade goods from all over the world can be found at the port of Samudera Pasai. The types of commodity goods that came from outside the Sultanate of Samudera Pasai were tombstones and ceramics. Meanwhile, the types of commodities that came from Samudera Pasai or locally were pepper and pottery.